Solution-processed single-crystalline organic transistors on patterned ultrathin gate insulators - Tsurumi, J.; Amin, Atefeh Y.; Okamoto, T.; Mitsui, C.; Takimiya, K.; Matsui, Hiroyuki; Halik, Marcus; Takeya, Jun (Organic Electronics, 2014)
Single-crystalline organic transistors of 3,11-didecyl-dinaphtho[2,3-d:2′,3′-d′]benzo[1,2-b:4,5-b′]dithiophene (C10-DNBDT-NW) and 2,9-didecyl-dinaphtho[2,3-b:2′,3′-f]thieno[3,2-b]thiophene (C10-DNTT) were fabricated by solution processes on top of the patterned hybrid ultrathin gate dielectrics consisting of 3.6 nm-thick aluminum oxide and self-assembled monolayers (SAMs). Due to the excellent crystallinity of the channel films, bottom-gate and top-contact field-effect transistors exhibited the average field-effect mobility of 3.7 cm2/V s and 4.3 cm2/V s for C10-DNBDT-NW and C10-DNTT, respectively. These are the first successful devices of solution-processed single-crystalline transistors on ultrathin gate dielectrics with the mobility above 1 cm2/V s, opening the way to develop low-power-consumption and high-performance printed circuits.